Establishing the Duration of Crimes: An Individual Differences and Eye‐Tracking Investigation into Time Estimation. Issue 2 (28th November 2013) - Attard, Janice; Bindemann, Markus
Summary The time available for viewing a perpetrator at a crime scene predicts successful person recognition in subsequent identity line‐ups. This time is usually unknown and must be derived from eyewitnesses' duration estimates. This study therefore compared the estimates that different individuals provide for crimes. We then attempted to determine the accuracy of these durations by measuring observers' general time estimation ability with a set of estimator videos. Observers differed greatly in their ability to estimate time, but individual duration estimates correlated strongly for crime and estimator materials. This indicates that it might be possible to infer unknown durations of events, such as criminal incidents, from a person's ability to estimate known durations. We also measured observers' eye movements to a perpetrator during crimes. Only fixations on a perpetrator's face related to eyewitness accuracy, but these fixations did not correlate with exposure estimates for this person. The implications of these findings are discussed. Copyright © 2013 John Wiley & Sons, Ltd.